2000
DOI: 10.1097/00005650-200001000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geographic Proximity to Cardiac Revascularization Services on Service Utilization

Abstract: Even across a relatively small geographic area, shorter distance to services and availability of services at the nearest hospital were strongly related to increased utilization of cardiac revascularization services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
67
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 33 publications
7
67
3
Order By: Relevance
“…[61][62][63][64][65][66][67][68][69][70][71] Several studies have found that women who lived farther away from facilities were less likely to undergo mammography than those who lived closer to facilities. [72][73][74][75][76] Contrary to those results, a study of the relationship between distance or travel time and adherence to screening mammography recommendations in rural Michigan failed to find an association.…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63][64][65][66][67][68][69][70][71] Several studies have found that women who lived farther away from facilities were less likely to undergo mammography than those who lived closer to facilities. [72][73][74][75][76] Contrary to those results, a study of the relationship between distance or travel time and adherence to screening mammography recommendations in rural Michigan failed to find an association.…”
Section: Discussionmentioning
confidence: 99%
“…31 Most studies of the association between distance and health care utilization have examined this relationship among residents of rural areas or large regions such as states that include areas of varying rurality. [32][33][34][35][36] Intraurban variation in the spatial accessibility of mammography and other health care services and its effect on residents' utilization is not well understood. 37 Facilities providing low-or no-fee screening mammography may be particularly important resources for midlife women (ages 40-64) residing in economically disadvantaged neighborhoods.…”
Section: Introductionmentioning
confidence: 99%
“…We offer these GIS techniques as an alternative to the current practice of arbitrarily locating new facilities on the basis of perceptions about patient demand. These findings may be applicable when planning the locations for future healthcare services for other chronic diseases requiring regular medical follow-up such as diabetes, cardiovascular disease, cancer, and chronic respiratory illnesses (13)(14)(15)(16)(17)(18)20,25).…”
Section: Discussionmentioning
confidence: 97%
“…However, the use of GIS techniques to determine the optimal location of a healthcare facility with the goal of optimizing patient access is limited (12,18,20,25). Given Canada's vast size and relatively sparse population, GIS techniques have the potential to inform decisions on location of healthcare facilities including planning for clinics to care for people with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%